ANALISIS PERKEMBANGAN SOSIAL DAN MORAL SISWA KELAS 1 SD PAB 23 PATUMBAK - Azzahra, Hanifah; Alesky, Alfito; Simanullang, Cindy; br Sembiring, Desi Mertina; Pakpahan, Godman Lesmana; Delvia, Putri; Ramadhani, Suci (Jurnal Merah Putih Sekolah Dasar, 2023)
This research aims to (1) determine the characteristics of social and moral development in elementary schoolaged children, and (2) to determine the implications of children's social and moral development for the formation of social attitudes in elementary school-aged children. The research method used in this research is research by direct observation. The results of the research show that the social and moral development characteristics of elementary school children are aware of the social roles, religion, race and socio-economic status of their peers, accept cultural stereotypes and adult attitudes towards This status gives rise to group awareness in behaving in their social environment. These characteristics will remain until childhood and will continue until they are adults if educators provide stimulus to continue their developmental tasks in a mature manner. This stimulus takes the form of guidance, direction, and provides a good and healthy social and cultural environment for social, emotional and moral development so that it has implications for the formation of good social attitudes. Keywords: social development, moral development, elementary school students